Comportamento da vida em fadiga de junta soldada do aço LN-700 - Esmelindro, Oséias Matias de Oliveira (2015)
In the present work was analyzed, in ideal welding power by the welding process metal active gas (MAG), the behavior of fatigue life in a welded joint of HSLA USI-LN-700 steel, which, due to its characteristics of chemical composition and thermo mechanical processing, is classified as high strength low alloy. Sought reduce of heat input and consequently the heat-affected zone (HAZ), to maintain the mechanical properties close to the base metal properties. It was decided to perform the robotic welding to ensure the repetitiveness of the parameters. In order to assess the fatigue strength compared with the material without weld tensile tests were performed, where the results of the yield stress had no significant variation between the samples with and without welding analyzed. The hardness profile demonstrated a little variation between the weld metal, HAZ and base metal, contributing to an increase in the number o cycles in the fatigue test. The verification of microstructural behavior resulted in an area thermally affected by the heat, an increase in grain size, as provided in the literature and, finally, the fatigue test revealed after the welding process in the USI-LN-700 steels, the there was a significant reduction in fatigue strength compared to base metal.